ISDN: The telecommunications highway for Europe after 1992 or Paving a dead end street?: The politics of pan-european telecommunications network development - Gerhard Fuchs (Max-Planck-Institut für Gesellschaftsforschung, 1993)
The paper examines the policies of the Commission of the European Community (CEC) aiming towards a coordinated introduction of an Integrated Services Digital Network (ISDN) in all member countries by 1993. Originally, ISDN was supposed to be a new telecommunications network that would eventuallyreplace the old telephone network. The analysis shows, however, that the ISDN activities of the CEC have been somewhat trapped between the attempt toliberalize the hitherto closed and fragmented European telecommunications markets on the one hand and the aim to build up a strong, independent European telecommunications industry and a Europe-wide telecommunications network on the other. At present, ISDN deployment is far behind schedule, and it will not fulfill the expectations of the Commission. Nevertheless, the CEC has established itself as an agenda-setting actor in European telecommunications policy. – – Die vorliegende Arbeit analysiert die Bestrebungen der Kommission der Europäischen Gemeinschaft, ein Diensteintegrierendes Digitales Fernmeldenetz (ISDN) europaweit bis 1993 einzuführen. ISDN war ursprünglich als ein Telekommunikationsnetz geplant worden, das das alte Telefonnetz ersetzen sollte. Die Analyse zeigt, daß die auf ISDN bezogenen Aktivitäten der Kommission von einer Ambiguität gekennzeichnet sind, die den Erfolg der Initiative gefährdeten: auf der einen Seite wollte die Kommission eine neue Infrastruktur mit Hilfe und zur Unterstützung der Monopolnetzbetreiber und der mit ihnen verflochtenen Nachrichtentechnikunternehmen aufbauen; auf der anderen Seite versuchte die Kommission, die fragmentierten und abgeschotteten nationalen Märkte und Monopole aufzubrechen. Der Status der ISDN-Einführung bleibt daher weit hinter den ursprünglichen Erwartungen zurück. Trotzdem hat es die Kommission geschafft, sich als neuer und entscheidender Akteur in der europäischen Telekommunikationspolitik zu positionieren.
Keywords: 300